THE INFLUENCE OF INSTITUTIONAL OWNERSHIP, INDEPENDENT OMMISSIONER, AUDIT COMMITTEE, FIRM SIZE AND LEVERAGE TO TEGRITY OF FINANCIAL STATEMENT ON MANUFACTURERS LISTED IN INDONESIAN STOCK EXCHANGE - Susilowati, Yeye; Sari, elen Puspita; Yuseno, Anton (Proceeding Fakultas Ekonomi, 2017)
The study is aimed to analyze the influence of Institutional Ownership, Independent Commissioner, Audit Committee, Firm Size and Leverage to Integrity of Financial Statement on Manufacturers listed in Indonesia Stock Exchange 2013-2015. The sample of this study is 305 companies listed in Indonesian Stock Exchange in 2013-2015. Selection of sample uses purposive sampling method with logistic regression analysis. The result of analysis shows that Institutional Ownership and Firm Size positively significantly influence Integrity of Financial Statement, Independent Commissioner and Audit Committee negatively not significantly influence Integrity of Financial Statement, and Leverage positively not significantly influences Integrity of Financial Statement. Keywords: Integrity of Financial Statements, Institutional Ownership, Independent Commissioner, Audit Committee, Firm Size and Leverage